Descriptive epidemiological study and impact on mental health and quality of life in patients with fibromyalgia at a Rheumatology Center (Brazilian Journal of Health Research, 2024)
Introduction: Fibromyalgia (FM) is a chronic syndrome associated with fatigue, sleep, mood and cognitive disorders and generalized musculoskeletal pain. Objectives: Evaluate the clinical profile of patients with FM, the most used treatments and the impact of this syndrome through specific scales. Methods: Descriptive study based on data from records from the Epifibro 2.0 Project of patients treated in an outpatient clinic of a Rheumatology Service, who met the American College of Rheumatology Diagnostic Criteria of 2010 for FM. Data collection was carried out through the application of questionnaires from the Epifibro 2.0 Project with epidemiological data and specific scores to evaluate the impact of FM on patients in the pain outpatient clinic of a Rheumatology service. The data were stored in an Excel spreadsheet and analyzed using the SPSS 20.0 program. Results: 69 patients were evaluated, with a mean age of 58.27 ±9.62 years and a predominance of females at 94,2%. It was observed that 59.4% of patients had been diagnosed for more than 10 years, 92.8% had completed high school and 86.7% had a family income greater than 3 minimum wages. The most prescribed medications were pregabalin and fluoxetine, whereas the most recommended non-pharmacological treatments were aerobic exercises. The means of the PDS, FIQR, GAD-7, PHQ-9 questionnaires were moderate to severe. Conclusion: The patients analyzed had long-lasting illness and the most prescribed treatment was pharmacological treatment associated with aerobic exercise. The questionnaires demonstrated a population with moderate to severe impact on mental health and quality of life.
Keywords: Fibromyalgia; Epidemiology; Quality of life; Database